Small Fiber Polyneuropathy Is Associated With Non–Bladder-Centric Interstitial Cystitis/Bladder Pain Syndrome Patients. Issue 9 (September 2021) - Overholt, Tyler L.; Matthews, Catherine A.; Evans, Robert J.; Badlani, Gopal; Ahn, Christine; Simon, Trang; Walker, Stephen J.
Abstract : Objectives: Interstitial cystitis/bladder pain syndrome (IC/BPS) comprises at least 2 phenotypes. Bladder centric patients typically demonstrate low bladder capacity (BC), often with Hunner lesion (HL), whereas non–bladder-centric patients typically have normal cystoscopic findings and more co-occurring nonurologic symptoms/syndromes (NUS), contributing to widespread pain beyond the bladder. Small fiber polyneuropathy (SFPN) is significantly associated with fibromyalgia, a frequent IC/BPS codiagnosis and may play an etiologic role in IC/BPS. We assessed SFPN status in bladder-centric versus non–bladder-centric IC/BPS patients. Methods: Distal leg biopsies were obtained from 11 IC/BPS patients after therapeutic hydrodistention. Specimens were embedded/sectioned per standard protocol and stained for protein gene product 9.5, an intraepidermal nerve fiber marker. To determine SFPN status, intraepidermal nerve fiber density was calculated and compared with normative reference values stratified by age/sex. The SFPN prevalence and reported comorbidities were compared between low BC and/or HL-positive ( bladder-centric ) versus non–low BC, HL ( non–bladder-centric ) patients. Results: Seven patients (63.6%) were SFPN positive. Non–bladder-centric patients demonstrated significantly more SFPN (6/7, 85.7%) compared with bladder-centric patients (1/4, 25.0%; P = 0.027). Non–bladder-centric patients also reported more comorbid NUS overall (1.25 ± 0.83 vs 5.86 ± 2.47; P = 0.003), including fibromyalgia ( P = 0.010), migraines ( P = 0.035), anxiety/panic disorder ( P = 0.035), allergies ( P = 0.027), and asthma ( P = 0.035). Conclusions: In this pilot study, SFPN was significantly more common in non–bladder-centric IC/BPS, that is, those patients who also reported greater prevalence of NUS, including fibromyalgia, migraines, anxiety/panic disorders, allergies, and asthma. These findings suggest that SFPN may have an etiologic role in a larger, systemic pain syndrome and should be explored further.